Cytokine response and damages in the lungs of aging Syrian hamsters on a high-fat diet infected with the SARS-CoV-2 virus - Fomin, Gleb; Tabynov, Kairat; Islamov, Rinat; Turebekov, Nurkeldi; Yessimseit, Duman; Yerubaev, Toktasyn (Frontiers in Immunology, 2023)
Hypertriglyceridemia, obesity, and aging are among the key risk factors for severe COVID-19 with acute respiratory distress syndrome (ARDS). One of the main prognostic biomarkers of ARDS is the level of cytokines IL-6 and TNF-α in the blood. In our study, we modeled hyperglyceridemia and hypercholesterolemia on 18-month-old Syrian hamsters (Mesocricetus auratus). By 18 months, the animals showed such markers of aging as weight stabilization with a tendency to reduce it, polycystic liver disease, decreased motor activity, and foci of alopecia.The high-fat diet caused an increase in triglycerides and cholesterol, as well as fatty changes in the liver. On the third day after infection with the SARS-CoV-2 virus, animals showed a decrease in weight in the groups with a high-fat diet. In the lungs of males on both diets, there was an increase in the concentration of IFNα, as well as IL-6 in both males and females, regardless of the type of diet. At the same time, the levels of TNF-α and IFN-γ did not change in infected animals.Morphological studies of the lungs of hamsters with SARS-CoV-2 showed the presence of a pathological process characteristic of ARDS. These included bronchointerstitial pneumonia and diffuse alveolar damages. These observations suggest that in aging hamsters, the immune response to pro-inflammatory cytokines may be delayed to a later period. Hypertriglyceridemia, age, and gender affect the severity of COVID-19. These results will help to understand the pathogenesis of COVID-19 associated with age, gender, and disorders of fat metabolism in humans.